2019
DOI: 10.1111/jpc.14704
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Buruli ulcer in Australia

Abstract: Aim: This study describes an Australian cohort of paediatric Buruli ulcer (BU) patients and compares them with adult BU patients. Methods: Analysis of a prospective cohort of all BU cases managed at Barwon Health, Victoria, from 1 January 1998 to 31 May 2018 was performed. Children were defined as ≤15 years of age. Results: A total of 565 patients were included: 52 (9.2%) children, 289 (51.2%) adults aged 16-64 years and 224 (39.6%) adults aged ≥65 years. Among children, half were female and the median age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…Note that in Australia, some studies have shown a predominance of the disease in adult subjects (Yerramilli et al, 2017;Walker et al, 2019). This discrepancy between our study and that of Nigeria could be explained by differences between the study periods.…”
Section: Discussioncontrasting
confidence: 99%
“…Note that in Australia, some studies have shown a predominance of the disease in adult subjects (Yerramilli et al, 2017;Walker et al, 2019). This discrepancy between our study and that of Nigeria could be explained by differences between the study periods.…”
Section: Discussioncontrasting
confidence: 99%
“…3 Optimal specimen collection includes two cotton swabs from beneath the undermined edges of the ulcer, or punch biopsies from edges of the lesion. 4 Due to significant necrosis from the production of mycolactone, lesions are often polymicrobial. Treatment of M. ulcerans should be prioritised, although secondary bacterial infection has been postulated to delay wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical suspicion ensures appropriate samples are collected, including fresh tissue for microbiological and PCR investigations, as well as formalin‐fixed for histopathology, although unfortunately diagnostic delays persist in non‐endemic areas 3 . Optimal specimen collection includes two cotton swabs from beneath the undermined edges of the ulcer, or punch biopsies from edges of the lesion 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this well-resourced highincome (HI) setting, early diagnosis followed by appropriate combination of antibiotic therapy and the judicious use of adjunctive plastic surgery has a near 100% treatment success rate. 8,9 The emerging public health threat BU is known as Bairnsdale ulcer or Daintree ulcer in Australia. 8 The disease is highly focal, with endemic and non-endemic areas separated by only a few kilometres.…”
Section: Introductionmentioning
confidence: 99%